2014
DOI: 10.1111/acem.12378
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Physicians Maintain Performance on the American Board of Emergency Medicine Continuous Certification (ConCert) Examination

Abstract: Objectives: The American Board of Emergency Medicine (ABEM) Maintenance of Certification (MOC) program is a four-step process that includes the Continuous Certification (ConCert) examination. The ConCert examination is a validated, summative examination that assesses medical knowledge and clinical reasoning. ABEM began administering the ConCert examination in 1989. The ConCert examination must be passed at least every 10 years to maintain certification. This study was undertaken to determine longitudinal physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…The aging physician is an important topic as it has been estimated that over one‐quarter of all actively licensed physicians in the United States are older than 60 years . A 2014 study concluded that emergency physicians maintain performance on the ConCert examination over the course of their careers . While this study showed relatively steady performance, it included only first attempts in each 10‐year certification cycle, leaving out a substantial group of physicians who failed previous attempts to pass the ConCert examination, but take the examination again.…”
mentioning
confidence: 97%
“…The aging physician is an important topic as it has been estimated that over one‐quarter of all actively licensed physicians in the United States are older than 60 years . A 2014 study concluded that emergency physicians maintain performance on the ConCert examination over the course of their careers . While this study showed relatively steady performance, it included only first attempts in each 10‐year certification cycle, leaving out a substantial group of physicians who failed previous attempts to pass the ConCert examination, but take the examination again.…”
mentioning
confidence: 97%
“…Certification and maintenance of certification in medical specialties evaluate a physician's cognitive and practice performance, with the goal of improved quality of medical care . A previous study demonstrated that over time, EPs maintained performance on the ConCert examination, demonstrating that they maintain medical knowledge and diagnostic processing over the course of their careers …”
Section: Discussionmentioning
confidence: 99%
“…Prior analysis has shown that the ABEM QE was a psychometrically stable examination prior to 2004, and has remained stable. 14 Eligible participants included all graduates of ACGME-accredited EM residency programs taking What was known and gap Studies have found varying impacts of duty hour limits on graduates' performance on board certification examinations, a key educational outcomes measure.…”
Section: Methodsmentioning
confidence: 99%